Implicações do câncer de mama no labor e na vida das mulheres mastectomizadas - Cardoso, Silvana Goncalves (2022)
Labor is a significant and impacting factor in contemporary life. It is fundamental in social integration, a reason for pleasure and personal fulfillment, and, paradoxically, can also be a source of illness. Despite advances in its treatment, breast cancer (BC) is the most common type of cancer among women and represents a public health problem in countries where high levels of income concentration, low effectiveness of public policies aimed at raising awareness and prevention in primary care for the early diagnosis of the disease. A new physical/psychological condition can lead to an absence from occupation and make the financial and social life of women who undergo BC treatment difficult. This study aimed to understand the implications of breast cancer in the occupation and life of women with mastectomy (MW). This is a descriptive cross-sectional study with a quantitative approach. Participated in the research (N=96; 16%) of women who underwent mastectomy surgery at the Clinical Hospital of Brazilian Hospital Office Service Company of the Federal University of Uberlandia- MG (HC/EBSERH/UFU), from 2013 to 2019. A questionnaire containing 20 multiple-choice questions and one discursive question was applied, using Google forms technology, in the online mode with the support of telephone contacts. Descriptive analysis was used. The social, professional, demographic and income profile of the MW was traced: (n= 48; 50.00%) are married/stable union and (n= 48; 50.00%) are widows/single/divorced/separated; (n=44; 45.80%) in their sixties; (n=52; 54.2%) white, highlighting a small number (n=10: 10.42%) of black women; (n=86; 89.60%) are mothers, with an average of 1.67 children; Incomplete elementary school (n=30; 31.25%) and complete high school (n=17; 17.71%) stood out; monthly income plays an important role and financial implications in the family context, with the predominant (n= 67; 69.80_%) having income between one to three minimum wages and standing out (n= 20; 20.83%) without income; in contrast to the number of retirees (n=43; 44.79%); it was observed (n= 69; 71.89%) of MW who participate in the economic life of the family, being responsible for the sustenance/support of the family or sharing this responsibility with other members. It was found that (n= 73; 76%) of the MW do not perform paid occupation, and (n= 23; 24%) do so and took an average of 6 to 18 months away from their occupation activities during treatment of the CM. (N=52; 54.2%) underwent partial mastectomy, with complications related to the postoperative period of the breast being frequent, highlighting in descending order: shoulder pain and difficulty in raising the arms (n = 46; 47.9%) ; tingling in the hands (n =44; 45.8%); change in libido (n =16; 16.7%); and lymphedema (n=15; 15.6%). When sharing their experiences, psychological support was verified as a recurring and relevant factor for MW, along with the support networks of friends, family, and religiosity, recognized as fundamental. All MW reported satisfaction and adequate care received with the treatment of professionals at HC/EBSERH/UFU. It is essential to develop care policies and sensitization the professionals and managers involved, in search of a healthy and successful return to the occupation of the MW. Promote comprehensive health care that identifies emotional, self-image, social, and leisure changes, in addition to physical and functional limitations. Information contributions, financial assistance and adaptations/relocations in the workplace, and the implementation of care delivery models with approaches focused and interested in the person, to the detriment of the disease, will result in women who are able to live the meaning of life with dignity and health.